2022
DOI: 10.3390/jmse10030418
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Microplastics in Sediment Cores from Two Mangrove Areas in Southern Thailand

Abstract: Mangroves are areas that connect the land and sea, and are important to the ecosystem. They are important places for food sources and the habitat of aquatic fauna in the tidal areas. However, the existence of plastic debris poses a risk to the aquatic environment. This study aimed to investigate the accumulation of microplastics (MPs) in sediment cores from two mangrove areas. The first mangrove area is in the outer section of the Songkhla lagoon (SK), while the second is in the coastal area of Pattani provinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 55 publications
3
13
0
Order By: Relevance
“…The microplastics found in this study were mostly in fiber form, as in previous studies in mangrove core sediments in southern Thailand, Hangzhou Bay, China, and Northern Vietnam (Li et al, 2020a;Luu Viet et al, 2021;Pradit et al, 2022). Moreover, many previous studies also suggested that the fiber type is detected as a major shape of microplastics in mangrove environments (biota: (Hastuti et al, 2019;Klangnurak and Chunniyom, 2020), sediments: (Mohamed Nor and Obbard, 2014;Wang et al, 2020;Zuo et al, 2020)).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The microplastics found in this study were mostly in fiber form, as in previous studies in mangrove core sediments in southern Thailand, Hangzhou Bay, China, and Northern Vietnam (Li et al, 2020a;Luu Viet et al, 2021;Pradit et al, 2022). Moreover, many previous studies also suggested that the fiber type is detected as a major shape of microplastics in mangrove environments (biota: (Hastuti et al, 2019;Klangnurak and Chunniyom, 2020), sediments: (Mohamed Nor and Obbard, 2014;Wang et al, 2020;Zuo et al, 2020)).…”
Section: Discussionsupporting
confidence: 85%
“…Accordingly, the microplastics found in this study can be implied as sourced from households around the study area. Besides the microplastics found in mangrove sediment cores from Pattani and Songkhla, southern Thailand, rubber and paint have been reported (Pradit et al, 2022). Other synthetic particles were also discovered associated with plastic polymers in this study, and the µ-FTIR analysis identified compounds of small particles, tire rubber, pigment, paint, dyes, and flame retardant.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…MP particles were identified, counted, and characterized (shape, size, and color) by visual identification under a stereomicroscope (Leica, EZ4W; Switzerland, Europe) with the Leica Application Suite program. We also applied the Hidalgo-Ruz et al (2012) rules mentioned in Pradit et al (2022a) to assist in identifying the MPs most encountered in this study. The rules were as follows: rule 1 = no cellular or organic structures visible, rule 2 = fibers should be equally thick throughout their entire length, and rule 3 = particles should exhibit homogenous color throughout the item.…”
Section: Methodsmentioning
confidence: 99%
“…Plastic waste in aquatic ecosystems has become a local, regional, and global issue. Several million tons of plastic waste are released into the marine environment through rivers and atmospheric particles ( Chen et al, 2021 ; Pradit et al, 2022a ). Microplastics (MPs) are plastic debris defined as particles less than 5 mm ( NOAA, 2009 ) and are classified as marine waste.…”
Section: Introductionmentioning
confidence: 99%